(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article reports the experience of actress and PPGAC/UDESC master’s student Kauana Machado in the workshop “Voice as Practice”, led by Meredith Monk and Ellen Fisher. The four-day artistic residency took place in December 2025 in Garrison, New York (USA). The experience combined meditation, singing, dance, and collective creation dynamics. Written by Machado and Miranda, the text connects the exercise routine to concepts such as “extended vocal technique” and “shadow play,” asking how bodily and vocal experiences shape feelings of community belonging and cultural identity.